“Rostov Text” and Context of A.T. Averchenko’s Creativity between 1918-1919th (Proceedings of Southern Federal University. Philology, 2021)
Viktoria D. Milenko (Sevastopol, Russian Federation)The author of the article for the first time refers to a little-known period in the biography of the writer-humorist A.T. Averchenko, who visited the Don in 1918-1919th. Cooperating with the local newspaper “Priazov Region”, Averchenko created a multi-genre “Rostov text”, which now numbers 26 publications and served as the material for the study. The biographical context allows to recreate publications in the magazines “New Satyricon”, “Theatrical Courier”, “The Don Wave”, the writer’s archive, memoirs of his contemporaries, etc.The relevance of the topic of the article is due to both the need for a scientific study of the biography of the emigrant writer and the tasks of literary local history, in particular, the possible perpetuation of Averchenko´s name in Rostov-on-Don (for example, with the memorial plaque on the building of the former editorial office of “Priazov Region”).Having indicated the characteristic feature of Averchenko’s creative path – touring activities – the author of the article sets the dates of his concerts in Rostov-on-Don in 1912, 1914, 1918, names the addresses (Asmolovsky theater, cafe “Empire”, theater “Grotesque”, etc.) and contacts in the civil and military spheres of the city. For the first time Averchenko’s way from Petrograd to the south in 1918 is reconstructed in details, the reasons of his departure from the capital are in many ways illuminated in a new way, littleknown data about his wife, opera singer E.F. Petrenko are introduced into scientific circulation. The reviews of the Averchenko´s Rostov concerts of humor are analyzed. Particular attention is paid to the civic self-determination of the writer, who for the first time found himself in the epicenter of the White Movement on the Don and supported it. Averchenko’s further social activities in Crimea are largely characterized as a logical continuation of the Rostov period, which together explains the reasons of his emigration.Key words: Arkadiy Averchenko, «New Satyricon», satiricon writers, «Rostov text», pamphlet, feuilleton, interviews, «Priazov Region», miniature theater «Grotesque», miniature theater «House of the Artist».DOI 10.18522/1995-0640-2021-2-166-179